Multiplexing methods in dynamic protein crystallography - Klureza, Margaret A; Pulnova, Yelyzaveta; von Stetten, David; Owen, Robin L; Beddard, Godfrey S; Pearson, Arwen R; Yorke, Briony A (Methods in enzymology, 2024)
Time-resolved X-ray crystallography experiments were first performed in the 1980s, yet they remained a niche technique for decades. With the recent advent of X-ray free electron laser (XFEL) sources and serial crystallographic techniques, time-resolved crystallography has received renewed interest and has become more accessible to a wider user base. Despite this, time-resolved structures represent < 1 % of models deposited in the world-wide Protein Data Bank, indicating that the tools and techniques currently available require further development before such experiments can become truly routine. In this chapter, we demonstrate how applying data multiplexing to time-resolved crystallography can enhance the achievable time resolution at moderately intense monochromatic X-ray sources, ranging from synchrotrons to bench-top sources. We discuss the principles of multiplexing, where this technique may be advantageous, potential pitfalls, and experimental design considerations.
Keywords: Synchrotrons; krystalografie rentgenová; Protein Conformation; konformace proteinů; synchrotrony; Crystallography, X-Ray; molekulární modely; proteiny; Proteins; databáze proteinů; Models, Molecular; Databases, Protein